Study guides

Q: Multiply x plus 3 x plus 4?

Write your answer...

Submit

Related questions

(x+3)(x+4)=x2+7x+12

(x+3)(x+4) = x2+7x+12

It is 123.99

Multiply out the factors and then you can check: (x + 2)(x + 3) = x² + 3x + 2x + 6 = x² + 5x + 6 ≠ x² + 3x + 4 Therefore False.

No. It simplifies to a monomial.

Question: 2 x 3 x 4 Answer: It's easier to break this down into separate parts. First, multiply 2 x 3 = 6 Then multiply 6 (which is 2 x 3) x 4 = 24 Therefore, 2 x 3 x 4 = 24

(x+3)(x+4) = x²+7x+12

4x + 4 or 4(x + 1)

(x + 3)(x + 4) = x2 + 7x + 12

3 plus 4 x plus 5 31 when simplified would give x = 23/4.

All you have to do is multiply 3 x 3 and you get 9.

216

It is: (-10)+(-3)+4 = -9

x/2+3=4 x/2=1 (take away 3 from both sides) x=2 (multiply both sides by two)

1

3 x 3 x 7 x 7

3 + 4 + 4 x 15 = 67

X 3 plus x-142 plus x is an equation equal to x3+2x-142.

It is: (x+3)(x+4) when factored

119.96 + 4 + 3 + 576 + 4 + 3 + 4.5 = 714.46

x^3+x^2+4x+4

x/3x + 4 = 4 1/3.

3 x 3 x 3 x 5 = 135

You simply multiply the expression on the outside (in this case, 3) by each of the expressions inside the parentheses, and add everything up. In this case, 3x + 3 times 4.

3 x 3 x 4 x 5 if you multiply them.